1995
DOI: 10.3109/02699059509008218
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of head injury: Implications for service planning

Abstract: As most of those experiencing traumatic brain injury tend to be young, disabled survivors will be gradually accruing in each locality as each year passes. How many need continuing care a decade after injury? How many need day care, or need help with finding work, or continuing support for carers? 190 patients who had been admitted to two UK regional neurosurgical units on average some 7 years earlier were followed up. With an average age of 29 years these patients stayed in hospital for an average 33 days. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 14 publications
(7 reference statements)
1
20
0
Order By: Relevance
“…Some studies suggest a general trend of increasing rates of RTW and full-time employment with greater elapsed time since injury (Stambrook et al, 1990). In reviewing the literature of long-term vocational outcomes of at least 10 years post-injury, there is also marked variation in RTW rates (Miller & Stern, 1965;Adey, 1967;Rusk, Block & Lowman, 1969;Bruckner & Randle, 1972;Dresser et al, 1973;Lundholm, Jepsen & Thomval, 1975;Gilchrist & Wilkinson, 1979;Lewin, Marshall & Roberts, 1979;Reyes, Bhattacharyya & Heller, 1981;Sweeney & Smutok, 1983;Thomsen, 1984;Rappaport, HerreroBacke, Rappaport & Winterfield, 1989;Tate, Lulham, Broe, Strettles & Pfaff, 1989;Thomsen, 1992;Kraft, Schwab, Salazar & Brown, 1993;Schwab, Grafman, Salazar & Kraft, 1993;Sbordone, Liter & Pettler-Jennings, 1995;Tennant, MacDermott & Neary, 1995). The percentage of subjects returning to work ranged from 38.9% to 75%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest a general trend of increasing rates of RTW and full-time employment with greater elapsed time since injury (Stambrook et al, 1990). In reviewing the literature of long-term vocational outcomes of at least 10 years post-injury, there is also marked variation in RTW rates (Miller & Stern, 1965;Adey, 1967;Rusk, Block & Lowman, 1969;Bruckner & Randle, 1972;Dresser et al, 1973;Lundholm, Jepsen & Thomval, 1975;Gilchrist & Wilkinson, 1979;Lewin, Marshall & Roberts, 1979;Reyes, Bhattacharyya & Heller, 1981;Sweeney & Smutok, 1983;Thomsen, 1984;Rappaport, HerreroBacke, Rappaport & Winterfield, 1989;Tate, Lulham, Broe, Strettles & Pfaff, 1989;Thomsen, 1992;Kraft, Schwab, Salazar & Brown, 1993;Schwab, Grafman, Salazar & Kraft, 1993;Sbordone, Liter & Pettler-Jennings, 1995;Tennant, MacDermott & Neary, 1995). The percentage of subjects returning to work ranged from 38.9% to 75%.…”
Section: Introductionmentioning
confidence: 99%
“…The actual nature of employment was described in five studies documenting very long-term outcomes of 10 years or more (Dresser et al, 1973;Kraft et al, 1993;Rusk et al, 1969;Thomsen, 1984Thomsen, , 1992. Other studies differentiated work into categories as full-time, part-time and self employed (Dresser et al, 1973;Rappaport et al, 1989;Sweeney & Smutok, 1983;Tate et al, 1989;Tennant et al, 1995;Thomsen, 1984Thomsen, , 1992, and some also used change in social position to describe vocational outcome (Bruckner & Randle, 1972;Lundholm et al, 1975) (see Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…The study was undertaken an average of 4 years post injury. 26 In another study 27 it was found that QL was severely reduced for those TBI persons who could not occupy their time.…”
Section: Introductionmentioning
confidence: 99%
“…TBI causes huge upheaval to family life; once discharged from hospital, many patients require continuing care (Tennant et al, 1995) and the responsibility of care is mostly provided by family members and spouses (Knight et al, 1998). Statutory services in the UK provide acute care and a limited range of rehabilitative services.…”
Section: Introductionmentioning
confidence: 99%